Grób z Beremian nad Dniestrem – rewizja wyników badań z XIX wieku. Ze studiów nad grupą białopotocką kultury komarowskiej - Romaniszyn, Jan; Gwizdała, Marta; Makarowicz, Przemysław (Muzeum Archeologiczne w Krakowie, 2016)
The article presents a re-analysis of results of the 19th-century research carried in one of the graves from the burial ground of the Biały Potok group of the Komarów culture in Beremiany, in Ukraine. Field-walking prospection was repeated, archaeological (a stone cist with contents) and anthropological materials (skeletons of the dead) were analysed. Obtained results indicate that a male and a female of the adultus age, equipped with a “Komarów-style” vessel and a bronze twisted pin with a disc-shaped (nail-like) head, were buried in the grave, most probably beneath a barrow. Radiocarbon dating determined the chronology of the grave at the 1st half of the 18th century B.C.
Keywords: grupa białopotocka; kamienna cysta; kurnan; epoka brązu; grób zbiorowy